SYNTHESIS AND ELECTROCHEMICAL CHARACTERIZATION OF Li3PO4 FORSOLID STATE ELECTROLYTES - Heri Jodi; Supardi Supardi; Evvy Kartini; Anne Zulfia (Jurnal Sains Materi Indonesia, 2016)
SYNTHESIS AND ELECTROCHEMICAL CHARACTERIZATION OF Li3PO4 FORSOLID STATE ELECTROLYTES. The application of solid state electrolytes to solid state battery becomes important research area, recently, to overcome leakage and combustion issues involved in liquid electrolytes. Solid state electrolytes are safer, easily packaged and have several advantages, including easy fabrication, high ionic conductivity at room temperature and wide compositional range. Here in this study we characterized Li3PO4 for solid state electrolyte, synthesized by solid state reaction and wet chemical reaction methods. The samples were characterized using Electrochemical Impedance Spectrometer (EIS) to determine its electrical properties in addition to X-Ray Diffraction and Scanning Electron Microscope -Energy Dispersive X-Rays Spectroscopy (SEM-EDS) characterizations. Both of samples that have been characterized have a high electrical resistivity on the order of tens MW, with DC conductivity in order of 10-10 to 10-9 S/cm.